Model teams games tournament melalui permainan bakiak berbasis LVE sebagai wahana peningkatan aktivitas motorik siswa sekolah dasar - Dicky Rasmana Putra Anjasmara; Rahmad Khodari; Auliya Aenul Hayati (Physical Education Departement of University PGRI Jombang, 2026)
This study was conducted to examine the effect of the Teams Games Tournament learning method, combined with the Living Values Education approach through clogs-walking activities, on the development of elementary school students’ motor skills, as well as to describe the process of instilling character values during the learning activities. The research method used was a combination of quantitative and qualitative approaches with an explanatory sequential design, in which numerical data collection was conducted first and then deepened through descriptive data. The quantitative phase employed a One-Group Pretest-Posttest design involving 19 third-grade students at SDN Mindi II in Majalengka Regency. Students’ motor skills were measured using the Test of Gross Motor Development, Second Edition (TGMD-2), while the qualitative instrument consisted of an observation sheet for Living Values Education, covering cooperation, tolerance, and responsibility. Quantitative data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, the paired-sample t-test, and the calculation of Cohen’s d effect size. The research data showed that the average Gross Motor Quotient score increased from 81.21 before the intervention to 89.26 after the learning program was implemented. The results of the paired-sample t-test showed a significance value of 0.001 (p < 0.05) with a Cohen’s d value of 1.469, which falls into the large effect category. The results of the qualitative observations also indicate gradual progress in the areas of cooperation, tolerance, and responsibility among students during the learning process. Therefore, the implementation of the TGT-LVE model through the bakiak game is effective in improving motor skills and supporting the overall character development of elementary school students.